Complementing Tissue Testing With Plasma Mutation Profiling Improves Therapeutic Decision-Making for Patients With Lung Cancer - Choudhury, Yukti; Tan, Min-Han; Shi, Jun Li; Tee, Augustine; Ngeow, Kao Chin; Poh, Jonathan; Goh, Ruth Rosalyn; Mong, Jamie (Frontiers in Medicine, 2022)
Background: Tissue biopsy is an integral part of the diagnostic approach to lung cancer. It is however invasive and limited by heterogeneity. Liquid biopsies may complement tissue testing by providing additional molecular information and may be particularly helpful in patients from whom obtaining sufficient tissue for genomic profiling is challenging. Methods: Patients with suspected lung cancer (n=71) were prospectively recruited. Blood and diagnostic tissue samples were collected within 48 hours of each other. Plasma cell-free DNA (cfDNA) testing was done using an ultrasensitive amplicon-based next-generation sequencing (NGS) panel (plasma NGS testing). For cases diagnosed as non-small cell lung carcinoma (NSCLC) via histology or cytology, targeted testing for epidermal growth factor receptor (EGFR) mutations was performed using tissue biopsy samples (tissue EGFR testing), where available. Concordance of clinically actionable mutations between methods and sample types were assessed. Results: For confirmed NSCLC cases (n=54), tissue EGFR test results were available only for 70.3% (38/54) due to sample inadequacies, compared to blood samples for 98.1% (53/54) cases. Tissue EGFR testing identified sensitizing EGFR (L858R or exon 19 deletion) mutation in 31.6% (12/38) of cases. Plasma NGS identified clinically actionable mutations in 37.7% (20/53) of cases, including EGFR mutations in two cases with no tissue EGFR results, and mutations in KRAS, BRAF and MET. Overall sensitivity of sensitizing EGFR mutation detection by plasma NGS was 75% (9/12), and specificity was 100% (25/25) in patients tested in both tissue EGFR and plasma NGS (n=37). In this cohort of patients, tissue EGFR testing alone informed clinical decisions in 22.2% (12/54) of cases. Adding plasma NGS to tissue EGFR testing increased the detection rate of actionable mutations to 42.6% (23/54), representing a 1.9-fold increase in clinically relevant findings. The average turnaround time (TAT) of plasma NGS was shorter than standard tissue testing (10 days vs. 29.9 days, p-value <0.05). Conclusions: In the first-line setting, plasma NGS was highly concordant with tissue EGFR testing. Plasma NGS increases the detection of actionable findings with shorter time to results. This study outlines the clinical utility of a complementary plasma mutation profiling in the routine management of lung cancer patients.